THEORETICAL ASPECTS OF THE ANALYSIS OF FAMILY TOURISM (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article is devoted to the analysis of problems and prospects for the development of family tourism. Theoretical aspects of the analysis of family tourism are considered, the basic concepts are characterized, the types, functions and tasks of family tourism are considered, and the features of family tourism as a type of tourism are revealed.